Quercetin, Hyperin, and Chlorogenic Acid Improve Endothelial Function by Antioxidant, Antiinflammatory, and ACE Inhibitory Effects. Issue 5 (13th April 2017) - Huang, Wu‐Yang; Fu, Lin; Li, Chun‐Yang; Xu, Li‐Ping; Zhang, Li‐Xia; Zhang, Wei‐Min
Abstract: In recent years, the blueberry cultivation and processing industry developed quickly because blueberries are super‐fruit with healthy function. Blueberry leaves are byproducts of the blueberry industry, which are rich in bioactive phenolics, such as quercetin (Q), hyperin (H), and chlorogenic acid (C). This study investigated protective effects of 3 phenolics (Q, H, and C) from leaves of rabbiteye blueberry Vaccinium ashei on human umbilical vein endothelial cells. The results showed that all these 3 phenolics could improve endothelial function by inhibiting oxidative damage and proinflammatory cytokines caused by tumor necrosis factor‐α (TNF‐α). The cell vitalities of endothelial cells pretreated with Q, H, and C were higher than those stimulated with TNF‐α only. These phenolics could decrease reactive oxygen species and xanthine oxidase‐1 levels and increase superoxide dismutase and heme oxygenase‐1 levels in endothelial cells. They also could decrease the protein expressions of intercellular adhesion molecule‐1, vascular cell adhesion molecule‐1, and monocyte chemotactic protein‐1 induced by TNF‐α. In addition, Q, H, and C also exhibited vasodilatory effect by reducing the angiotensin I–converting enzyme (ACE) protein levels in endothelial cells. Mostly 3 phenolics exhibited bioactivities as a function of concentration, but the effects not always depended on the concentration. The antioxidant and antiinflammatory effects of Q seemed to be more pronounced than H; however, H exhibited higher cell vitalities. The results indicated that phenolics from rabbiteye blueberry leaves could be potential antioxidants, inflammation and ACE inhibitors, and rabbiteye blueberry leaves provide a new resources of phytochemicals beneficial for cardiovascular health.